Conduction system pacing in pediatric and congenital heart disease - Chubb, Henry; Mah, Douglas; Dubin, Anne M.; Moore, Jeremy (Frontiers in Physiology, 2023)
Conduction system pacing (CSP) has evolved rapidly to become the pacing method of choice for many adults with structurally normal hearts. Studies in this population have repeatedly demonstrated superior hemodynamics and outcomes compared to conventional pacing with the recruitment of the native conduction system. Children and patients with congenital heart disease (CHD) are also likely to benefit from CSP but were excluded from original trials. However, very recent studies have begun to demonstrate the feasibility and efficacy of CSP in these patients, with growing evidence that some outcomes may be superior in comparison to conventional pacing techniques. Concerns regarding the technical challenges and long-term lead parameters of His Bundle Pacing (HBP) have been overcome to many extents with the development of Left Bundle Branch Area Pacing (LBBAP), and both techniques are likely to play an important role in pediatric and CHD pacing in the future. This review aims to assimilate the latest developments in CSP and its application in children and CHD patients.